Managing organizational factors to improve forecasting performance - Davis, Donna (Henry Stewart Talks, 2010)
Evaluating and monitoring effects of organizational factors on forecasting performance, Based on organizational learning theory, Framework linking forecasting climate, forecasting capability, performance outcomes, and performance measurement, Examples provided by managers at 18 global manufacturing firms